PEMBANGUNAN APLIKASI E-COMMERCE DALAM MENUNJANG PENJUALAN PRODUK PADA CV.RIZTECH - Rahmad Syah; Muhammad Iqbal; Marischa Elveny (Teknik Informatika Universitas Malikussaleh, 2014)
CV. Riztech is a company engaged in the sale of apparel products that have not implemented electronic commers to market products that exist in the distribution of clothing. So as to support product sales and balancing competitiveness among similar companies. Business processes are carried CV.Riztech at this point with the type of commerce business to customer (B2C). The process of selling products made by small amounts, the products are sold only be booked for mid-scale, and usually the customer who ordered the product. This study focuses on supporting the company's sales by marketing the product as a built-E-Commerce online have the feature that: Administrative Tools (Backend Office), shoping Features (Frontend), Security, and Communication.